Epidemiological and clinical features of Plasmodium falciparum malaria in united nations personnel in Western Bahr el Ghazal State, South Sudan. - Dengming He; Yuqi Zhang; Xiaofeng Liu; Shimin Guo; Donghong Zhao; Yunjie Zhu; Huaidong Li; Li Kong (PLoS ONE, 2013)
Western Bahr el Ghazal State is located in northwestern South Sudan, which is a tropical area subject to Plasmodium falciparum malaria epidemics. The aim of this study is to explore the epidemiological and clinical features of Plasmodium falciparum malaria in United Nations personnel stationed in this area. From July 2006 to June 2009, epidemiological data and medical records of 678 patients with Plasmodium falciparum malaria at the U.N. level 2 hospital were analyzed. The U.N. personnel were divided into individuals not immune to Plasmodium falciparum and individuals semi-immune to Plasmodium falciparum. The patients were divided into a chemoprophylaxis group (non-immune individuals who complied with the chemoprophylaxis regimen, 582 cases) and a no/incomplete chemoprophylaxis group (non-immune individuals who either did not fully comply with chemoprophylaxis or did not use it at all and semi-immune individuals who did not use chemoprophylaxis, 96 cases). Overall morbidity was about 11.3%. There was a significant difference in the morbidity of semi-immune and non-immune individuals (1.3% vs. 15.1%, P<0.001). Out of the total, 82.9% of cases occurred during the rainy season. The incidence of fever in the chemoprophylaxis group was significantly lower than in the no/incomplete chemoprophylaxis group (36.8% vs. 96.9%, P<0.001). Significant differences were observed between the two groups with respect to all other malaria-like symptoms except gastrointestinal symptoms, serum glucose level, platelet count, and alanine aminotransferase level. The incidence of complications was 1.2% (chemoprophylaxis group) and 44.8% (no/incomplete chemoprophylaxis group).The most common complication was thrombocytopenia, which was seen in 40.6% of the no/incomplete chemoprophylaxis group. In summary, Plasmodium falciparum malaria mainly occurred in rainy season. Gastrointestinal symptoms are an important precursor of malaria. Blood smears and rapid diagnostic tests should be performed after the onset of gastrointestinal symptoms. Appropriate chemoprophylaxis is necessary for reducing the severity of malaria.